Wastewater treatment in tropical, vertical up-flow constructed wetlands with selected macrophytes species: A preliminary analysis - Muhammedziyad Geleto; MihretDananto Ulsido; YohannesSeifu Berego (Heliyon)
The aim of this study was to investigate the growth characteristics of different local macrophyte species (n = 7) capable of growing in untreated coffee wastewater, select the dominant species for use in mesocosms, to study the efficacy of three major species in three replications (3 x 3) in improving the physicochemical characteristics of coffee wet mill wastewater, and to assess the contribution of macrophyte biomass to nutrient sequestration in the constructed wetlands. The current study showed that Polygonumhydropiperoides(PH), Chrysopogonzizanioides (CZ), and Cyperusexaltatus(CE) can sustain water logging and partially saturated conditions. The conducted wetland experiments pointed out the feasibility of VUFCW technology in ameliorating the impurities in wet coffee processing mills wastewater. Each of the three plant species has a peculiar ability to trap potential impurities. Cyperusexaltatus, for instance, is significantly efficient (α < 0.05) in reducing turbidity, minimizing PO43− and NO3−, and sequestrating it in the biomass as compared with the other two macrophytes. Polygonumhydropiperoides is good at improving DO; and Chrysopogonzizanioides is good at pH, EC, and TDS reduction. Therefore, the most effective constructed wetland can be designed by combining the three macrophytes vitalizing the ultimate potential of each of them in the system. However further studies and extended data collections are needed to ensure the enhanced quality of wastewater through the plant based treatment methods.